Modeling the impact of hospital logistics on quality of care and patient satisfaction: Results of a survey in three public healthcare facilities in Fez, Morocco - Youness Frichi; Fouad Jawab; Said Boutahari (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: The objective of this research is to examine the role of hospital logistics in improving quality of care and patient satisfaction. Thus, the paper focuses on modeling and evaluating the relationship between these three constructs. Design/methodology/approach: In the present study, hospital logistics was specified as a second-order construct composed of five first-order constructs: physical accessibility, waiting time, consultation time, hospital hotel services, and administrative procedures. A questionnaire was developed and administered face-to-face to 384 hospitalized patients in three public healthcare facilities in Fez-Morocco. Collected data were processed and analyzed deploying the PLS-SEM method and using SmartPLS3 software. Data analysis was carried out by considering two types of patient circuits according to the admission modes in the healthcare facility: Urgent Patients Circuit and Scheduled Patients Circuit. Thus, two PLS-SEM models were evaluated and validated. Findings: Results highlighted the significant impact of hospital logistics on quality and satisfaction. In particular, the results of the two models showed that the most preponderant hospital logistics component is physical accessibility which consists of the availability and accessibility of ambulances, medical and nursing staff, support and guidance staff, technical facilities and equipment, etc. Thus, hospital managers and health system stakeholders should pay particular attention to hospital logistics activities in general and specifically to the physical accessibility to improve the quality of care and patient satisfaction. Research limitations/implications: This study only included patients from three public healthcare facilities in Fez-Morocco. Also, the model variables of hospital logistics construct are restricted and were applied in a specific context. Besides, the sample size was relatively reduced. Thus, results generalization might be limited. Further studies including more patients from other territories and including other logistics components are needed for large-scale validation of the proposed model. Originality/value: The results of this study contribute to the scientific literature on hospital logistics and its role as a lever for quality of care and patient satisfaction.
Keywords: 650; Hospital logistics; quality of care; patient satisfaction; modeling; PLS-SEM; Morocco